Combined assessment of septal scar and septal flash by cardiac magnetic resonance identifies responders to cardiac resynchronization therapy. (4th February 2022) - Kjellstad Larsen, C; Duchenne, J; Galli, E; Aalen, JM; Lederlin, M; Bogaert, J; Kongsgaard, E; Linde, C; Penicka, M; Donal, E; Voigt, J-U; Smiseth, OA; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): South-Eastern Norway Regional Health Authority. Research grants of the University of Leuven. Background: Left ventricular (LV) scar, particularly in the lateral wall and septum, reduces response rate to cardiac resynchronization therapy (CRT), whereas a dyssynchronous LV contraction pattern (septal flash) suggests good response. Lateral wall scar abolishes septal flash. Therefore, a combined approach of septal scar and septal flash may characterize the myocardial substrate responsive to CRT. Cardiac magnetic resonance (CMR) may assess both scar and contraction pattern. Purpose: The present study aimed to determine if combined assessment of septal scar and septal flash by CMR as single image modality identifies responders to CRT. Methods: We investigated all CRT recipients with available CMR from a prospective, multicenter study (n = 136), with both ischemic and non-ischemic heart failure. Septal scar was assessed by late gadolinium enhancement (LGE) from a stack of short axis slices (n = 128) and septal flash determined visually on ordinary cine sequences (n = 136). CRT response was defined as ≥15% reduction in LV end-systolic volume by echocardiography at 6 months follow-up. We also assessed heart transplantation or death of any cause 39 ± 13 months after device implantation. Results: In multivariate analysis including percentage septal scar (LGE), septal flash, QRS-duration and QRS-morphology, septal LGE and septal flash were the only independent predictors of CRT response (both p < 0.001). A combined approach of septal LGE and septal flash predicted CRT response with area under the curve 0.86 (95% confidence interval (CI): 0.78-0.94) and long-term survival without heart transplantation with hazard ratio 0.18 (95% CI: 0.05-0.61). A practical approach to selection of CRT candidates by septal LGE and septal flash is illustrated in the present figure. As shown, absence of septal LGE indicated excellent response rate (93%) to CRT independent of other parameters. When septal LGE was present, however, overall response rate was substantially lower (58%), but presence or absence of septal flash separated responders from non-responders with high accuracy. This sequential approach correctly classified 86% of patients. Importantly, the approach was equally accurate in patients with intermediate QRS duration (130-150ms), where 93% of patients were correctly classified. Conclusions: Combined assessment of septal LGE and septal flash by CMR as single image modality identifies CRT responders with high accuracy and predicts long-term survival.